Applying the routine activity approach to crime victimization in rural Southeast Asia - Ulrike Grote; Thanh Tung Nguyen; Trung Thanh Nguyen; Frank Neubacher (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
We use a panel dataset of around 3.500 rural households from Southeast Asia and investigate evidence on crime victimization. More concretely, we ask (1) to what extent are rural people in Thailand and Vietnam affected by crime? And (2) what factors determine rural crime victimization? We use the routine activity approach as the theoretical framework and apply different logit models to identify determinants of crime victimization. We find that 5.46% of the rural households have been victimized, mainly by theft, over the last 12 months, some of them even more than once. Living in a rural region with higher levels of inequality is positively correlated with the likelihood of theft victimization. Households with higher levels of crop commercialization are associated with a higher victimization risk, while households with more livestock and being more specialized in specific livestock species are associated with a lower risk. Moreover, past victimization and exposure to weather shocks are positively associated with the likelihood of being affected by crime. We conclude that rural crime requires attention although overall incidence is low in rural Thailand and Vietnam. Guardianship should be promoted, especially in times of weather shocks. Finally, reducing inequality helps preventing theft.
Keywords: D1; I3; K14; K4; O1; Q1; 330; Farm crime; Victimization; Routine activity approach; Logit model; Southeast Asia